Media discourses about a superspreader destination: How mismanagement of Covid-19 triggers debates about sustainability and geopolitics. (November 2021) - Mayer, Marius; Bichler, Bernhard Fabian; Pikkemaat, Birgit; Peters, Mike
Abstract: Winter sport destinations received increased attention from worldwide media due to their Covid-19 superspreader status. Using a critical media discourse analysis ( N = 1036) for the case of Ischgl, Austria this paper 1) identifies crisis-specific media discourse patterns, 2) analyzes the embedding of discourses in prevailing public debates and 3) discusses the responsibility of media coverage. Our findings reveal scapegoating patterns reinforced by destination image but later replaced by fundamental discussions about the sustainability of Alpine winter sports. As the crisis lasted longer, Ischgl became a meta-symbol for failures in dealing with Covid-19, with media coverage increasingly detached from the local situation, initiating a geopolitical blame game and highlighting media's responsibility for post-crisis tourism. Highlights: The study examines media discourses related to Covid-19 and tourism. Media coverage about ski destinations as superspreader reached high intensity. Discourses moved from the crisis situation to tourism sustainability in general. The destination Ischgl became a meta-symbol for failures in dealing with Covid-19. Results show the negative perspective of media reports on tourism and its actors.